Prevalence of RTIs among women of reproductive age group in Shimla city - Parashar A; Gupta B; Bhardwaj A; Sarin R (Wolters Kluwer Medknow Publications, 2006)
Objective : To find out the prevalence of RTIs among women of reproductive age group. Study design: Cross-Sectional Study. Setting and Participants : Women of reproductive age group in 25 Municipal Wards of Shimla City. Study period : March 1999 to October 1999. Sample size : 600 women between 15-49 years age. Study variables : Education, marital status, age at marriage, socioeconomic status, menstrual hygiene practices, contraceptive practices, parity. Results : The study was undertaken based on syndromic approach for RTIs. Based on the complaints of the patients, laboratory investigations were also undetaken. Overall prevalence of RTIs was found to be 36.3% and this prevalence was significantly related to mean age at the marriage, marital status, parity, menstrual hygiene practices, current contraceptive method use and socioeconomic status.